2019
DOI: 10.1371/journal.pone.0225435
|View full text |Cite
|
Sign up to set email alerts
|

The association between cigarette smoking and serum thyroid stimulating hormone, thyroid peroxidase antibodies and thyroglobulin antibodies levels in Chinese residents: A cross-sectional study in 10 cities

Abstract: ObjectivesAlthough several studies have shown that cigarette smoking is associated with thyroid stimulating hormone (TSH), thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb), the exact relationship between smoking and thyroid function is controversial. As little is known about the effects of smoking on TSH, TPOAb and TgAb in Chinese residents. This study aimed to evaluate the association between cigarette smoking and TSH, TPOAb and TgAb in ten-city residents of China.Study designThis was a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 53 publications
1
18
1
Order By: Relevance
“…In population surveys in Western countries (151,152), current smokers have a lower prevalence of the autoantibodies associated with autoimmune thyroiditis (151,152), though this association may depend on iodine status (152,153) and findings in Asia have been mixed (see e.g. (153)(154)(155)(156)). Data regarding the association of smoking with thyroiditis itself are conflicting.…”
Section: Cigarette Smoking Inflammation Cell Proliferation and Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In population surveys in Western countries (151,152), current smokers have a lower prevalence of the autoantibodies associated with autoimmune thyroiditis (151,152), though this association may depend on iodine status (152,153) and findings in Asia have been mixed (see e.g. (153)(154)(155)(156)). Data regarding the association of smoking with thyroiditis itself are conflicting.…”
Section: Cigarette Smoking Inflammation Cell Proliferation and Thyroid Cancermentioning
confidence: 99%
“…Given these uncertainties, an anti-inflammatory effect of smoking is also not a convincing explanation for the inverse association of smoking with thyroid cancer. Another proposed explanation for a reduced risk of thyroid cancer in smokers is the lower levels of thyroid stimulating hormone (TSH, thyrotrophin) that has been documented in current smokers in population surveys ( (152,156,163,164)). TSH is a growth factor for thyrocytes, and suppression of TSH secretion is used in the treatment of thyroid cancer (165).…”
Section: Cigarette Smoking Inflammation Cell Proliferation and Thyroid Cancermentioning
confidence: 99%
“…About the confounders, observations in the first stage indicate that age, female sex, and higher BMI increase the probability of positive TPOAb, but smoking has a protective role in most variants. Previously, the protective effect of smoking on developing HT and the production of anti-thyroid antibodies such as TPOAb and TgAb have been reported (20,21). In longitudinal approach, we found that increasing age did not always increase the likelihood of TPOAb positivity.…”
Section: Discussionmentioning
confidence: 39%
“…About the confounders, observations in the first stage indicate that age, female sex and higher BMI, increase the probability of positive TPOAb, but smoking has a protective role in most variants. Previously, the protective effect of smoking on developing Hashimoto's Thyroiditis and the production of anti-thyroid antibodies such as TPOAb and TgAb have been reported (20,21). In longitudinal approach, we found that increasing age did not always increase the likelihood of TPOAb positivity.…”
Section: Discussionmentioning
confidence: 43%